PENGUKURAN UNJUK KERJA MODULASI GMSK PADA SOFTWARE-DEFINED RADIO PLATFORM - Eko Marpanaji; Bambang Riyanto; Armein Z.R. Langi; Adit Kurniawan (Universitas Ahmad Dahlan, 2007)
This paper addresses performance measurement of Gaussian Minimum Shift Keying (GMSK) modulation which is implemented on Software-Defined Radio (SDR) platform using Universal Software Radio Peripheral (USRP) from GNU Radio. GMSK modulation is very popular and is adopted as GSM cellular phone modulation standard. The results of this research can be used as basic concept in developing wireless communication system based on SDR technology which is needed in Next-Generation Networks (NGN). The GMSK performance is measured in terms of Packet Error Rate (PER) with several of Eb/No, bit rate, modulation frequency, payload size, and gain values. Based on this research, the lowest PER can be achieved by setting Eb/No value equal to 20 dB, optimum bit rate = 256 kbps, BT 0.25, optimum payload size = 4092 bytes, and optimum gain equal to 100.